RFID technology for aerospace supply chain: application perspectives / Mohd Khir Harun …[et al.] - Harun, Mohd Khir; Mokhtar, Ahmad Zahir; Ahmad Shah, Shahrul; Alias, Ahmad Jais (2006)
RFID (Radio Frequency IDentification) is a new technology that is starting to have significant impact on the aerospace supply chain management. It has become an increasingly recognised technology with its strong tracking and tracing ability at a much greater level of accuracy, real-time and providing more value at each step in the supply chain. With the aerospace environments becoming more and more competitive, and their information systems are sharing the fundamental information of assuming rather than knowing where and what things are, RFID technology provides the solution for closing the gap between the physical flow of materials and the information flow in the production system. In this paper, RFID technology is reviewed with respect to various application aspects in the aerospace manufacturing and maintenance industry in the light of enhancing manufacturing intelligence and delivering added-on values. The applications include production planning, operation and quality control, product tracking, maintenance and repair, inventory tracking and visibility as well as labour productivity.